Rotavirus vaccine administration patterns in Italy: potential impact on vaccine coverage, compliance and adherence - Domenico Martinelli; Francesca Fortunato; Federico Marchetti; Rosa Prato (Taylor & Francis Group, 2021)
Acceptance of rotavirus (RV) vaccination may be impacted by several factors including the feasibility of the full schedule administration within the fixed immunization timelines. The human RV vaccine Rotarix (GSK) and the human bovine reassortant vaccine RotaTeq (Merck & Co.) were developed with different posologies (2 doses vs 3 doses respectively), which have both scientific and technical implications. A non-systematic literature review revealed that, in the Italian context, topics such as time to achieve RV protection in children, number of preventable cases and administration time window, compatibility/ease of inclusion in the national vaccination calendar, potential overlaps with the peak of natural history of intussusception and adherence to posology could be impacted by the RV vaccine posology. Results suggest that a shorter schedule would allow for greater flexibility of use as well as a greater documented ease of inclusion in the vaccination calendar, thereby reducing potential direct healthcare costs.